given �ç 1to-1 f(x)dx=0 and �ç 1to0 f(x)dx=5, compute the following
a.�ç 0to-1 f(x)dx
b.�ç 0to1 3f(x)dx=0
c.�ç 1to-1 (f(x)+7)dx=0
2 answers
ç is the integral sign
Using I for integral,
I f(x) dx [1,-1] = I f(x) dx [1,0] + I f(x) dx [0,-1]
I f(x) dx [0,1] = -I f(x) dx [1,0]
I 3f(x) dx = 3 * I f(x) dx
I (f(x)+7) dx = I f(x) dx + I 7 dx
Now just plug and chug...
I f(x) dx [1,-1] = I f(x) dx [1,0] + I f(x) dx [0,-1]
I f(x) dx [0,1] = -I f(x) dx [1,0]
I 3f(x) dx = 3 * I f(x) dx
I (f(x)+7) dx = I f(x) dx + I 7 dx
Now just plug and chug...